The Principal's Role as a Manager in Improving Learning Effectiveness - Rahman, Rahmania; Aring, Fendy Novten (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to describe and analyze issues related to the effectiveness of learning, such as low teacher discipline, insufficient instructional supervision, limited learning innovation, and the suboptimal use of technology. These conditions indicate that the principal’s role as a manager has not been fully effective. The principal plays an important role in managing all school assets to achieve learning that is effective, efficient, and oriented toward improving the quality of education. The approach used in this study is qualitative descriptive, with research respondents consisting of school leaders, educators, and administrative staff at the junior high school level. Data were collected through interviews, field observations, and document review, which were then processed using an interactive model that includes data reduction, data presentation, and conclusion drawing. The findings of this study indicate that the principal has carried out managerial duties optimally, covering the stages of planning, organizing, implementing activities, and controlling the learning process. In the planning function, the principal develops programs to improve learning quality by involving all school members. In the organizing function, the principal allocates teacher and staff responsibilities proportionally and forms effective work teams. During the implementation stage, the principal provides motivation, supervision, and support for teachers in applying innovative learning methods. Meanwhile, in the supervision function, the principal conducts continuous evaluations of teacher performance and student learning outcomes to ensure the effectiveness of the learning process. Overall, the results show that principals who effectively perform their managerial role are able to create a conducive learning environment, enhance teacher professionalism, and encourage active student participation in the learning process. Thus, the principal’s role as a manager contributes significantly to improving learning effectiveness and the quality of education in junior high schools.